Identification of Aedes aegypti in the southern region of Cochabamba, Bolivia - Ortega-Martinez, Rommer Alex (2024)
Objective. To determine the presence of Aedes aegypti in the southern region of Cochabamba(Bolivia) to establish an updated record. Methods. A descriptive, prospective, and ecological study was conducted in three districts (6, 8, and 9) of the southern region of the Cochabamba Department, Bolivia, located above 2500 meters above sea level. Ovitraps were used for vector identification and subsequent egg hatching. Results. One larva of Ae. aegypti and one of Culex were identifed in district 6. In district 8, seven Ae. aegypti larvae and nine adults were found, along with two pupae and fve eggs in different Territorial Base Organizations (OTBs). Additionally, 56 Culex eggs were identifed in districts 8 and 9, 93 Culex larvae in district 8, and more than 40 Culex adults in the same district. The dendrogram revealed two clusters: one comprising all life stages of both species and another containing only Culex eggs. Conclusions. It is essential to implement vector elimination programs to prevent further infections caused by this arbovirus, particularly Ae. aegypti.